Self-assembled PEGylated albumin nanoparticles (SPAN) as a platform for cancer chemotherapy and imaging - Jung Eun Lee; Myung Goo Kim; Yeon Lim Jang; Min Sang Lee; Nak Won Kim; Yue Yin; Jong Han Lee; Su Yeon Lim; Ji Won Park; Jaeyun Kim; Doo Sung Lee; Sun Hwa Kim; et al. (Taylor & Francis Group, 2018)
Paclitaxel (PTX) is used as a major antitumor agent for the treatment of recurrent and metastatic breast cancer. For the clinical application of PTX, it needs to be dissolved in an oil/detergent-based solvent due to its poor solubility in an aqueous medium. However, the formulation often causes undesirable complications including hypersensitivity reactions and limited tumor distribution, resulting in a lower dose-dependent antitumor effect. Herein, we introduce a facile and oil-free method to prepare albumin-based PTX nanoparticles for efficient systemic cancer therapy using a conjugate of human serum albumin (HSA) and poly(ethyleneglycol) (PEG). PTX were efficiently incorporated in the self-assembled HSA-PEG nanoparticles (HSA-PEG/PTX) using a simple film casting and re-hydration procedure without additional processes such as application of high pressure/shear or chemical crosslinking. The spherical HSA-PEG nanoparticle with a hydrodynamic diameter of ca. 280 nm mediates efficient cellular delivery, leading to comparable or even higher cytotoxicity in various breast cancer cells than that of the commercially available Abraxane®. When systemically administered in a mouse xenograft model for human breast cancer, the HSA-PEG-based nanoparticle formulation exhibited an extended systemic circulation for more than 96 h and enhanced intratumoral accumulation, resulting in a remarkable anticancer effect and prolonged survival of the animals.